Hypoglycemia post bariatric surgery: drugs with different mechanisms of action to treat a unique disorder - Giovanna Braganholo Carpentieri; Sandra Elisa Adami Batista Gonçalves; Walid Mohamed Mourad; Lara Guimarães Carelo Pinto; Maria Teresa Zanella (Archives of Endocrinology and Metabolism, 2023)
ABSTRACT Postprandial hypoglycemia (PPH) is a complex and multifactorial complication of bariatric surgery (BS). PPH may cause severe symptoms or be asymptomatic. The treatment of this condition requires dietary changes, but severe cases require drug therapy. The number of therapeutic options is limited and are often associated with adverse side effects. Different classes of drugs have been used and tested, but the resolution of PPH remains a challenge for physicians and patients. In this review, we gathered articles on PPH after BS from PubMed searches (2001 to 2022) and focused on the main drugs tested for the treatment of this condition, such as acarbose, somatostatin analogues, type 2 sodium-glucose cotransporter inhibitors, calcium channel blockers, and liraglutide. Avexitide and glucagon pump are two new therapeutic options that have been recently tested. For the search, the terms “postbariatric hypoglycemia,” “bariatric surgery,” and “late dumping syndrome” were used. PPH after BS is a frequent condition that should always be evaluated after BS. Treatment should be individualized and the available therapeutic options may be useful based on the condition's pathophysiology.